Carnosine alleviates diabetic nephropathy by targeting GNMT, a key enzyme mediating renal inflammation and fibrosis - Xue-qi Liu; Ling Jiang; Lei Lei; Zhen-yong Nie; Wei Zhu; Sheng Wang; Han-xu Zeng; Shiqi Zhang; Qiu Zhang; Benito A. Yard; Yonggui Wu (2020)
Abstract Diabetic nephropathy (DN) is a common microvascular complication of diabetes and the main cause of end-stage nephropathy (ESRD). Inflammation and fibrosis play key roles in the development and progression of diabetic nephropathy. By using in vivo and in vitro DN models, our laboratory has identified the protective role of carnosine (CAR) on renal tubules. Our results showed that carnosine restored the onset and clinical symptoms as well as renal tubular injury in DN. Furthermore, carnosine decreased kidney inflammation and fibrosis in DN mice. These results were consistent with high glucose (HG)-treated mice tubular epithelial cells (MTECs). Using web-prediction algorithms, cellular thermal shift assay (CETSA) and molecular docking, we identified glycine N-methyltransferase (GNMT) as a carnosine target. Importantly, we found that GNMT, a multiple functional protein that regulates the cellular pool of methyl groups by controlling the ratio of S-adenosylmethionine (SAM) to S-adenosylhomocysteine (SAH), was down-regulated significantly in the serum of Type 1 DM patients and renal tissues of DN mice. Moreover, using cultured TECs, we confirmed that the increased GNMT expression by transient transfection mimicked the protective role of carnosine in reducing inflammation and fibrosis. Conversely, the inhibition of GNMT expression abolished the protective effects of carnosine. In conclusion, carnosine might serve as a promising therapeutic agent for DN and GNMT might be a potential therapeutic target for DN.